IMPLMENTASI METODE PROFILE MATCHING PADA SISTEM PENDUKUNG KEPUTUSAN DALAM PEMBERIAN JABATAN KELAS PADA MAHASISWA - Fauzi, Muhammad (STMIK KAPUTAMA, 2019)
Each university has many students who are members of various fields. Fields that cover the departments at the university. The field represents the performance of each student and affects the status of students at the university. To improve discipline in every student and class. Then a class organization was formed which aimed as a liaison between students and students. Within the organization there are several positions for several students, namely the commissioner as chairman, vice chairman, secretary and treasurer. This is to bring together students in various circles in each class, the benefits of students being organized, increasing awareness, personality and mentality are good for the psychological development of students. To provide student positions, certain conditions are needed so that decisions can be considered fair. Therefore it is important for students to pay attention to several students who have the potential to be given positions in the classroom.